Changes in workplace situation and work values. Relations and dynamics within different employment regimes - Hauff, Sven; Kirchner, Stefan (management revue, 2014)
Workplace situation as well as work values have apparently changed in the last decades. However, up to now we do not know how these changes are related. This article considers both, workplace situation and work values, together and analyses theoretically and empirically how different developments can either lead to match or mismatch between workplace situation and work values. It refers to the employment regime approach to analyse the potential influence of different institutional frameworks. Findings have revealed various change patterns where developments regarding different dimensions of work life follow different logics: If employment becomes less secure, job security becomes more important. With respect to other dimensions (income, career opportunities, interesting job, and independence at work), an adaptation can be observed. The existing employment regime theory helps little in explaining the dynamics between workplace situation and work values.
CRIS-Team Scopus Importer:2025-04-09
Keywords: Employment regimes; Mismatch; Organisational change; Work value change